The Economic Valuation of Tourism Sector and Poverty Reduction in Kota Batu: Travel Cost Method (TCM) Approach - Wahyudi, Setyo Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Kota Batu, as one of the tourist destinations in East Java, has long been known as the best tourism destination. On the other hand, Kota Batu also still has a problem regarding poor people. The tourism sector is seen as a growth strategy that enables the economy to grow, has the potential to improve the local economy, and able to reduce poverty. This study aims to measure the economic valuation of the tourism sector and its contribution to poverty reduction. The respondents and research samples are visitors to the tourist village of Bumiaji District, Kota Batu. Using the travel cost method, the results of the study showed that the economic valuation of the tourist village of the Bumiaji District provided substantial value and ability to contribute to poverty reduction in the area. Village tourism visitors also benefit (consumer surplus) because of the relatively low average costs to be borne compared to the willingness to pay.